Leprosy Reactions: Experience in the Puerto Rico Hansen’s Disease Population - Rodriguez-Rivera, Diana V.; Pelet-del Toro, Natalia M.; Quintero-Noriega, Aida L. (Puerto Rico Health Sciences Journal, 2023)
Objective: Hansen’s disease (HD) is a chronic granulomatous infection endemic in the tropics. Its main clinical manifestations involve the cutaneous, nervous, and musculoskeletal systems. Leprosy reactions (LR) are systemic inflammatory and immune-mediated complications of HD. These include reversal reactions (RR), erythema nodosum leprosum (ENL), and Lucio phenomenon. These reactions significantly increase disease-related morbidity and disability. We aimed to determine the number and type of LR, their association to hosts’ immune responses (Ridley Jopling classification), timing of development, and treatment of HD patients in Puerto Rico. Methods: A retrospective medical record review was performed on 291 HD patients containing LR status data available from the Dermatology Service at the Hispanic Alliance for Clinical & Translational Research. Results: Our data revealed that 83 (29%) patients developed LR, of which 31% had RR and 69% had ENL. Most LR were observed in patients in the lepromatous border (97%): Borderline lepromatous leprosy (BL) and Lepromatous Leprosy (LL). Most patients with RR and ENL had a single episode (83% and 62%, respectively), and those that received multi-drug therapy (MDT) had a reaction onset occurring most frequently within the first year of MDT and after the first year of MDT, respectively. Prednisone was the first line treatment used to manage both types of LR. Conclusion: Most lepromatous reactions occur within the lepromatous border. ENL was the most common LR. Prompt recognition and management of these immunologic reactions is essential to prevent long term nerve function impairment.